IDEOLOGI DALAM PENERJEMAHAN BUDAYA: ANALISIS PADA NOVEL TERJEMAHAN â€œNEGERI 5 MENARAâ€ KARYA AHMAD FUADI - Fadly, Ahmad (Jurnal Pendidikan Bahasa dan Sastra, 2016)
AbstractThis research aims to describe the translation procedures, methods, and ideology applied to translate novel Negeri 5 Menara,and assess the impact of the ideology on equivalence. This research is using qualitative approach and content analysis. The source of data for this research consists of documents that refer to novel Negeri 5 Menara and its translation in English. The units of analysis of this research data comprise of words, phrases, sentences, and dialogue taken from Negeri 5 Menara Ahmad Fuadi’s Work and its translation (The Land of 5 Towers) by Angie Kilbane. Findings of this research show followings. First, translation procedures were used 90 times to render Negeri 5 Menara into English. On the basis of the frequent use of each translation procedures, functional equivalent (20) appears to be first rank, followed by cultural equivalent (19), reduction and couplets (10), transference and naturalization (7), descriptive equivalent (6), notes (4), transposition (3), and modulation and compensation (2). Second, theoretically, transference and naturalisation are oriented to source language while cultural equivalent, functional equivalent, descriptive equivalen, transposition, modulation, compensation, reduction, couplets, and notes are oriented to target language. This means that the translator tended to choose adaptation, free, idiomatic, and communicative methods. Third, the use of translation procedures and the selection the translation methods tend to be based on the adoption of the ideology of domestication. Fourth, in terms of the equivalence of the translations, it was found that 80 data were accurately translated and 10 data were inaccurately translated. Therefore, the domestication ideology has a good impact to the quality of translations.Keywords: ideology of translations, translation method, translation procedure, culture.